"The World's Back Womb?": Commercial Surrogacy and Infertility Inequalities in India. Issue 4 (23rd October 2014) - Singh, Holly Donahue
ABSTRACT While transnational commercial surrogacy in India has recently attracted the attention of journalists and feminist scholars critical of a novel and particularly intimate example of labor outsourcing, surrogacy in India is not only about global inequalities. In this research report, I call attention to silences in the most well‐known accounts of surrogacy to the persistent local inequalities that structure infertility treatment in general—and surrogacy in particular. I argue that the disappearance of medical professionals' perceptions of surrogates as "laborers" and of Indian infertility experiences in these accounts occurs not only because of significant challenges to data collection, but also because of widespread naturalization of inequality. Local inequalities that structure transnational surrogacy in India, in particular, and infertility treatment, in general, tend to escape the purview of examinations that employ a transnational frame. Most research on gestational surrogacy in India does not focus on the options available to Indians who face infertility. The few studies that put the dynamics of infertility among people living in India at the center of analysis have yet to explore fully the "reproscapes" of infertility among people in India. [surrogacy, infertility, inequality, India, transnational]